(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article aims to explore the significance of the physical environment and seating arrangement in effective EFL classrooms. Research shows that effective language learning depends not only on linguistic knowledge but also on psychological comfort and a properly organized physical space. This paper discusses the impact of the emotional atmosphere in the classroom, teacher-student relationships, the location of tables and chairs, and educational equipment on student motivation, activity, and communicative competence based on scientific sources. It also provides practical pedagogical recommendations for educational environments with limited resources.